Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1497710
|View full text |Cite
|
Sign up to set email alerts
|

Integration of suspended carbon nanotube arrays into electronic devices and electromechanical systems

Abstract: A synthetic strategy is devised for reliable integration of long suspended single-walled carbon nanotubes into electrically addressable devices. The method involves patterned growth of nanotubes to bridge predefined molybdenum electrodes, and is versatile in yielding various microstructures comprised of suspended nanotubes that are electrically wired up. The approach affords single-walled nanotube devices without any postgrowth processing, and will find applications in scalable nanotube transistors (mobility u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
153
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 16 publications
(19 reference statements)
6
153
1
3
Order By: Relevance
“…We succeeded in using refractory metals W and Pt/W (W as adhesive layer for Pt) as preformed electrodes and found that the typical resistance of our individual suspended SWNT devices was in the range of 10 -50 kΩ ( Figure 2 to 4). The contact resistance appeared higher than devices with nanotubes lying on substrates with Pd top-contacts [7,14] , but lower compared to other suspended SWNT devices including those with preformed Mo electrodes [4] or top-contacted Au electrodes [3] .…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…We succeeded in using refractory metals W and Pt/W (W as adhesive layer for Pt) as preformed electrodes and found that the typical resistance of our individual suspended SWNT devices was in the range of 10 -50 kΩ ( Figure 2 to 4). The contact resistance appeared higher than devices with nanotubes lying on substrates with Pd top-contacts [7,14] , but lower compared to other suspended SWNT devices including those with preformed Mo electrodes [4] or top-contacted Au electrodes [3] .…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6] Here, we report a reliable method for the fabrication of suspended SWNT devices with improved metalnanotube contacts and a useful double-gate design. These devices have led to the revelation of interesting electrical transport properties of nanotubes that are distinct from those pinned on substrates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent developments toward an industrially favorable SWNT transistor fabrication process include prepatterned catalysts where SWNTs selectively grow at the device sites, [20][21][22][23][24] and dispersing SWNTs over a surface in order to produce an entangled network. 25,26 In this paper, we report a three-step procedure that yields individually addressable arrays of high-throughput SWNT FETs.…”
Section: Introductionmentioning
confidence: 99%